PENGEMBANGAN BAHAN AJAR MEMBACA BAHASA INDONESIA UNTUK KELAS V SD DENGAN MODEL DICK DAN CAREY - Lilik Muntari (MEDIA DIDAKTIKA, 2016)
The development research for teaching reading based on Dick and Carey has two focuses of the research, nomely (1) The proccess of developing teaching matery reading based on Dick and Carey, (2) The quality of developing teaching matery reading based on Dick and Carey. The developing style four-D has four steps, namely, the first step is the definition that consist of early analisys, student analisys, concept analisys and formulation of study aims. The second in plan is ning the third development fourth is sharing. The development of data quality such as validity, effectivity, and practicality data. The validity based on the value of handbook from validator. The value of handbook is gotten from worth of content, the wordth of presentation, the wort of linguistic the wort of grafic. The effectivity based on the respond of the teachers and student to handbook. The particality based on observer value to student activity and the student description when learning about reading of Dick dan Carey.The result of this research is development of data proccess and the quality of developing data. On the grade of validity the worth of content has already reached total score 80,0. The worth of presentation get total score 89,09. The worth linguistic get total score 88,57. the worth of grafic get total score 88,88. the worth grade of efectifity get result 93,85.